Pengaruh Work Life Balance Terhadap Produktivitas Kerja Karyawan di Mercure Hotel Padang - Zulfa, Nada Huriyah; Adrian, Arif (Jurnal Kajian Pariwisata Dan Perhotelan, 2025)
This study is driven by the identification of issues related to work life balance on work productivity. This study will employ the following research methodology: the causal associative method with a quantitative approach, which seeks to determine the impact of work life balance on worker productivity. The quantity of samples used in this research was 90 respondents utilising the total sampling technique. Data collection in this study was obtained using a questionnaire that had been prepared with a Likert scale. The method of gathering data was done utilizing a questionnaire that had a Likert scale, it underwent reliability and validity testing. Data processing for this investigation was done utilising SPSS 25.00. The outcomes of this study indicate that the work life balance variable is in the sufficient category, specifically with an average value of the respondent's achievement level of 72.80%, and the work productivity variable shows a sufficient category with an average value of the respondent's achievement level of 74.74%. In the work life balance value (X), the calculated F value is 64.821 with Sig 0.000 <0.05, indicating that the work life balance variables able to clarify the work productivity variable significantly. Additionally,, the Adjusted R Square value obtained was 0.424, indicating that the influence of the motivation variable (X) on the visiting decision variable (Y) was 42.4%, while 57.6% was impacted by additional elements..